THE TEMPORAL RELATIONSHIP BETWEEN JOINTS AND FAULTS - Peacock D.C.P. (My University, 2001)
Examples are presented of three temporal relationships between joints and faults: joints that pre-date faults; joints that are precursors to, or synchronous with, faults; and joints that post-date faults. Emphasis is placed on strike-slip faults in carbonate beds, but other examples are used. General rules are given for identifying the three temporal relationships between joints and faults. Joints that formed before faults can be dilated, sheared or affected by pressure solution during faulting, depending on their orientation in relation to the applied stress system. Faulted joints can preserve some original geometry of a joint pattern, with pinnate joints or veins commonly developing where faulted joints interact. Joints formed synchronously with faults reflect the same stress system that caused the faulting, and tend to increase in frequency toward faults. In contrast, joints that pre- or post-date faults tend not to increase in frequency towards the fault. Joints that post-date a fault may cut across or abut the fault and fault-related veins, without being displaced by the fault. They may also lack dilation near the fault, even if the fault has associated veins. Joints formed either syn- or post-faulting may curve into the fault, indicating stress perturbation around the fault. Different joint patterns may exist across the fault because of mechanical variations. Geometric features may therefore be used in the field to identify the temporal relationships between faults and joints, especially where early joints affect or control fault development, or where the distribution of late joints are influenced by faults.